Biologically Important Coordination Compounds of Palladium(II) and Platinum(IV) with 2-Substituted Benzimidazole - Seth, Gita; Garg, Yajula (Asian Journal of Chemistry, 2010)
Palladium(II) and platinum(IV) chloride react with 2-substituted benzimidazole to give complexes of the formula MLCl where M = Pd (II) and Pt(IV), L = 1,2-bis(2-benzimidazolyl) ethanol (BBIE) and 1,2-bis(2-benzimidazolyl) ethane thiol (BBIET). These complexes have been characterized on the basis of elemental analysis, conductance measurement, IR and NMR studies. The square-planar geometry has been suggested for these complexes. These complexes have been evaluated for their fungicidal activity against Alternaria alternata and Aspergillus niger by spore germination inhibition method.